Organizational Performance of the Baubau City Library and Archives Service - Zainul Abidin; Neny Marwati; Andi Tenri (Sean Institute, 2024)
This study aims to describe the Organizational Performance of the Baubau City Library and Archives Service and the factors that influence the organizational performance of the Baubau City Library and Archives Service. This study is a qualitative descriptive study. Data analysis techniques through data collection, data reduction, data presentation, and drawing conclusions. The results of the study explain that the organizational performance of the Baubau City Library and Archives Service is the quality of service provided by library officers is good but not yet as expected due to the lack of employees and skills, which affects efficiency and effectiveness. The quality of organizational performance of the Baubau City Library and Archives Service can be said to be good even though there are some employees who are still unable to complete their tasks on time due to limited abilities and the minimum number of employees, the attitude of cooperation built in the Baubau City Library and Archives Service is very good, seen from the involvement of employees in official activities helping each other in completing work, the initiative taken by employees is by providing good ideas and by carrying out tasks without waiting for orders from superiors. Factors that affect the Organizational Performance of the Baubau City Library and Archives Service are always based on organizational goals to be the direction and guideline for all organizational activities. The organizational culture of the Baubau City Library and Archives Service shows a good work culture with a positive and mutually helpful work climate, The leadership applied to the Baubau City Library and Archives Service is a leadership that can protect its subordinates by providing work motivation, providing clear direction, and always being open to input and discipline, Limited human resources are not an obstacle to the implementation of services at the Baubau Library Service because services are still carried out, but the addition of the number of employees is still carried out so that the workload can be overcome.